DUKUNGAN INFORMASIONAL ORANG TUA: PENENTU KEBERHASILAN PRESTASI AKADEMIK ANAK DI PERDESAAN - Indrawati, Adelia Ratih; Alfiasari, Alfiasari (Jurnal Ilmu Keluarga dan Konsumen, 2016)
Academic achievement can be influenced by internal and external factors. External factors are including family, friend, and school environment that interact with children. This study aimed to analyze the social support received by children from the environment and also to analyze the role of the mother-child attachment to the academic achievement of elementary school children in rural areas. Participants were 100 primary school-age children who live in intact families in rural areas from the two selected primary schools in the study sites. The sampling technique was using proportional random sampling; based on the number and sex of the students in each selected schools. The study found that the better informational support of the parents, the better academic achievement of children. It is also found that the better mother-child attachment, the better academic achievement of primary school-age children in rural areas. However, regression test of the hyphothesis model, this study showed that only the informational support of the parent is the most significant determinant factor on the academic achievement of children in rural areas than the other variables.